Pengaruh Etika Bisnis Islam, Kualitas Produk, dan Harga Produk Terhadap Loyalitas Konsumen Produk Kosmetik Wardah (Studi Kasus: Konsumen Wanita Produk Wardah Kota Bandung) - Nuriswan, Aditya Daffa (Educationist: Journal of Educational and Cultural Studies, 2023)
This research aims to see how Islamic Business ethics, product quality, and price influence customer loyalty toward Wardah cosmetics. The research utilizes a quantitive methodology, and the data collection method is the distribution of an online questionnaire through the Google form platform. The questionnaire will be distributed to one hundred consumers of Wardah cosmetics in Bandung city using a technique of purposive sampling. The data will be analyzed utilizing multiple linear regression. Based on the research findings, it can be partially understood that islamic business ethics significantly influence consumer loyalty, with a significance value of 0,000 < 0,05. However, product quality does not significantly impact consumer loyalty, as its significance value is 0,301 > 0,05. Price significantly impacts consumer loyalty, with a significance value of 0,000 < 0,05. Meanwhile, simultaneously, there is an influence of islamic business ethics, product quality, and price on consumer loyalty, with a significance value of 0,000 < 0,05.